Livestock and Women's Livelihoods: A Review of the Recent Evidence - Kristjanson, Patricia M.; Waters-Bayer, Ann; Johnson, Nancy L.; Tipilda, A.; Njuki, Jemimah; Baltenweck, Isabelle; Grace, Delia; MacMillan, Susan (International Livestock Research Institute, 2010)
This paper synthesises evidence of the contributions that livestock make to the livelihoods of poor women in sub-Saharan Africa and South Asia and identifies factors that enhance or constrain livestock-related opportunities for women. We apply a gender lens to three livestock-related pathways out of poverty—securing, building and safeguarding livestock assets; increasing and sustaining livestock productivity; and enhancing participation in and benefits from livestock markets. For each pathway, we summarize what is known and what this knowledge implies for programmatic and policy interventions. Assembling this information is a first step towards identifying some of the large gaps in our evidence base as well as some indications of the kinds of research and development interventions, made in relation to which species and value chains, that appear most likely to benefit poor women and their families.